Utilizacion de la estadistica y el diseno experimental en investigacion en yuca - Mendoza, G.; Amézquita, María Cristina (International Center for Tropical Agriculture, 1978)
Emphasis is placed on the usefulness of statistics in analyzing exptl results. Definitions are given of basic concepts and terminology. The designs most frequently used in cassava expt are completely randomized, randomized complete blocks, split plots and systematic (response surface, fan-shaped and parallel rows), A brief description is given of how and when to use these designs, calculations needed for statistical analysis and examples to illustrate their use. (CIAT)